∫ 0 1 0 ⌊ ( x 2 + 1 6 4 ∣ x ∣ ) m ⌋ d x
Given that 1 lies between the roots (of y ) of the equation y 2 − m y + 1 = 0 , evaluate the integral above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Firstly m>2 .
Next as we are working in positive domain remove mod sign .
Next denominator is x+16/x which has a minimum value of 16 by AM-GM.
So The thing whose power is greater than 2 is less than 1 . hence greatest integer will give 0.
As simple as that!
f ( y ) = y 2 − m y + 1
Since the given parabola is opening upward and 1 lies between the roots of the equation f ( y ) = 0 ,
f ( 1 ) < 0 ⇒ 1 − m + 1 < 0 ⇒ m > 2
The integral has non-negative limits, hence we could use A.M - G.M .
2 x 2 + 1 6 ≥ x 2 ( 1 6 ) ⇒ x 2 + 1 6 4 ∣ x ∣ ≤ 2 1
⌊ ( x 2 + 1 6 4 ∣ x ∣ ) m ⌋ = 0 . . . . . . . . . ∵ a m < 1 when a < 1 & m > 0
So the integrand is zero.
Rest is trivial.
Note that since we are only integrating over the non-negative values, we could have simply dealt with x in place of ∣ x ∣ .
A slightly more interesting version of this problem would be to ask for ∫ − 1 0 1 0 ⌊ ( x 2 + 1 6 4 x ) 2 ⌋ d x .
@Challenge Master: The function ⌊ ( x 2 + 1 6 4 x ) 2 ⌋ is an even function. Hence the integral would reduce to:
I = 2 ∫ 0 1 0 ⌊ ( x 2 + 1 6 4 x ) 2 ⌋ d x = 0 since we are again evaluating this over non-negative x .
Problem Loading...
Note Loading...
Set Loading...
Let f ( y ) = y 2 − m y + 1
f ( 1 ) < 0 ⇒ m > 2
Let z = x 2 + 1 6 4 ∣ x ∣ = t 2 + 1 6 4 t . . . . ( t = ∣ x ∣ )
⇒ z t 2 − 4 t + 1 6 z = 0
Since ' t ' is real, D ≥ 0
⇒ 0 ≤ z ≤ 0 . 5 as z ≥ 0
0 ≤ z m ≤ 2 m 1 ⇒ [ z m ] = 0